2013
DOI: 10.4103/2249-4847.116406
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of persistent pulmonary hypertension of the newborn in neonatal intensive care unit of al-minya university hospital in Egypt

Abstract: Background:Persistent pulmonary hypertension of the newborn (PPHN) result from the failure of the normal fetal-to-neonatal circulatory transition is associated with substantial infant mortality and morbidity.Objective:To estimate the possible risk factors and assess the outcome of these cases.Materials and Methods:Prospective study was performed enrolling all full-term and post-term newborn admitted to the NICU from January 2009 to April 2012, All neonates were subjected to complete history and physical examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
9
30
1
Order By: Relevance
“…[25] Despite remarkable progress in understanding the pathophysiology and treatment of PPHN, [10,[11][12][13][14] the condition remains a treatment challenge for neonatologists, especially in developing countries, and the associated mortality rate remains high in resource-limited settings. [5][6][7][8][9]26,27] Of the 72 neonates included in our study, 51.4% were female and 52.8% were born by vaginal delivery. Birth weight was appropriate for gestation age in 80.6% of cases in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Despite remarkable progress in understanding the pathophysiology and treatment of PPHN, [10,[11][12][13][14] the condition remains a treatment challenge for neonatologists, especially in developing countries, and the associated mortality rate remains high in resource-limited settings. [5][6][7][8][9]26,27] Of the 72 neonates included in our study, 51.4% were female and 52.8% were born by vaginal delivery. Birth weight was appropriate for gestation age in 80.6% of cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The reported overall mortality ranges from 4% to 33% in developed countries [2] and from 25% to 48% in developing countries. [5,6] In South Africa (SA), previous studies reported the incidence of PPHN to be 1.1%, with a mortality rate of 31% at Tygerberg Children's Hospital [7] and 48% at Chris Hani Baragwanath Academic Hospital. [8] PPHN develops due to the failure of circulatory transition at birth, causing the pulmonary artery pressure to remain higher than systemic pressures.…”
Section: Researchmentioning
confidence: 99%
“…The most common underlying cause for PPHN in our study was meconium aspiration (53.8%), which was also supported by Abdel Mohsen, et al (50%). 4 Perinatal asphyxia-clear liquor (30.8%) was the second common cause for PPHN in our study. Our centre with limited resources, does not have 24hours ECHO.…”
Section: Discussionmentioning
confidence: 83%
“…At birth, B. Within 3 days after birth, C. >3 days after birth based on the study done by Abdel Mohsen, et al 4 The diagnostic modality before the first dose of sildenafil was divided as a) 4 limb Spo 2 alone b) 4 limb Spo 2 + ECHO. The outcome of PPHN and the overall outcome of the neonate was also noted.…”
Section: Other Factors Assessedmentioning
confidence: 99%
“…Caesarean section delivery was higher (50%-63.5%) among patients with PPHN as shown in various studies [3,5,6,7,9,10] in both developed and developing countries. In a study by Rocha et al from Portugal the percentage of deliveries by LSCS was 65.3%.…”
Section: Lscsmentioning
confidence: 91%